The sources of unemployment fluctuations: an empirical application to the Italian case - Silvia Fabiani; Alberto Locarno; Giampaolo Oneto; Paolo Sestito (European Central Bank (ECB), 2000)
The paper attempts at disentangling the main sources of the rise in the Italian unemployment rate over the last four decades on the basis of a small model a la Layard-Nickell, identified and estimated using a structural VAR approach. Unemployment movements are assumed to be driven by fully permanent and long-lived but temporary shocks. The component of unemployment related to current and lagged demand shocks deriving from the sVAR estimation is found to be relevant and quite persistent, its swings accounting for approximately a 4 percentage points change in the unemployment rate. In particular, while temporary by construction, this component shows an almost continuous increase since the beginning of the 1980s. Nonetheless, the results confirm that the bulk of the rise in Italian unemployment is to be attributed to non-demand factors: temporary (namely productivity and labour supply shocks) and fully permanent (namely shocks to the wage bargaining schedule). The latter explain a gradual rise of about 2.5 percentage points between the end of the 1960s and the beginning of the 1980s; over the last 15-20 years, however, they do not seem to have further contributed to the worsening of unemployment situation.
Keywords: C51; E24; J60; 330